Onyx embolization of dural arteriovenous fistulas of the cavernous sinus through the superior pharyngeal branch of the ascending pharyngeal artery. (28th April 2014) - Pero, Guglielmo; Quilici, Luca; Piano, Mariangela; Valvassori, Luca; Boccardi, Edoardo
Abstract : We report three cases of dural arteriovenous fistula (DAVF) of the cavernous sinus treated by Onyx injection through the superior pharyngeal branch of the ascending pharyngeal artery. The treatment of choice of DAVFs of the cavernous sinus is endovascular, and it is preferentially done via transvenous occlusion of the cavernous sinus. The cavernous sinus can be reached through either the inferior petrosal sinus or the superior ophthalmic vein. When these venous routes are occluded, the first attempt is to pass through the occluded inferior petrosal sinus, but sometimes this attempt can fail. In some cases there are small transosseous feeders to the fistula arising from the superior pharyngeal branch of the ascending pharyngeal artery. When all of the more conventional approaches are unattainable, this route can be attempted. In our experience, it allowed safe and rapid occlusion of the fistula.